Utilization of modified flour (maltodextrin) from yam starch for the manufacture of tomato extract encapsulate - Inda Three Anova; Kamsina Kamsina (Jurnal Litbang Industri, 2022)
Tomato (Solanum lycopersicum ) is a popular vegetable and functional food ingredient. It is typically used to make fruit juice, which is then consumed directly or in a mixed form. The content consists of water, fiber, vitamins, and minerals and functions as an antioxidant. Therefore, this study aimed to utilize modified flour from yam starch as maltodextrin to produce tomato juice encapsulant. Yam starch maltodextrin encapsulation treatment consisted of 5%, 10%, 15%, 20%, 25%, and 30% aquadest for tomato juice (1:1). The yield, moisture, ash, and vitamin C content were calculated. The 30% treatment produced the highest yield value of 194 g, with water and ash contents of 5.21% and 1.59%, respectively. Meanwhile, the 5% treatment had the highest vitamin C of 0.77%.